Calcium homeostasis in mitochondrion-mediated apoptosis of chick embryo cecal epithelial cells induced by Eimeria tenella infection. (February 2016) - Cui, Xiao-zhen; Zheng, Ming-xue; Zhang, Yan; Liu, Rui-li; Yang, Sha-sha; Li, Shan; Xu, Zhi-yong; Bai, Rui; Lv, Qiang-hua; Zhao, Wen-long
Abstract: In this study, the process of Eimeria tenella -induced apoptosis and the effect of calcium homeostasis were investigated in chick embryo cecal epithelial cells. In particular, we examined cytochrome c release into the cytoplasm, mitochondrial permeability transition pore (MPTP) opening, and changes in [Ca 2 + ]c and apoptosis in host cells. Apoptosis, MPTP opening, cytochrome c release, and [Ca 2 + ]c in host cells increased following infection. This trend was reversed by blocking the increase in [Ca 2 + ]c using BAPTA/AM and EGTA (intra- and extracellular chelators of Ca 2 +, respectively) and by applying heparin sodium and ryanodine (blockers of the inositol triphosphate and ryanodine receptors of the endoplasmic reticulum, respectively). These results indicate that [Ca 2 + ]c plays a significant role in host cell mitochondrial apoptosis, which is induced via modulation of extracellular Ca 2 + levels and endoplasmic reticulum Ca 2 + channels. Thus, agents that restore Ca 2 + homeostasis may be useful for managing E. tenella infection in chickens. Highlights: We examined the role of Ca 2 + in mitochondrial apoptosis during Eimeria tenella infection. Cytosolic [Ca 2 + ] and apoptosis increased in chick cecal epithelial cells infected by Eimeria tenella . The increases were abolished by blocking extracellular Ca 2 + influx and ER Ca 2 + channel release. Restoring Ca 2 + homeostasis can suppress apoptosis induced by Eimeria tenella infection.